STUDI PEMBUATAN DAGING TIRUAN DARI JANTUNG PISANG (Musa Acuminata) - Muhammad Said siregar; Dharma Amanda Tambunan; Syakir Naim Siregar (Agritech: Jurnal Fakultas Pertanian Universitas Muhammadiyah Purwokerto, 2022)
The research on the study making analog meat from flower banana (Musa Acuminata) with the method Completely Randomized Design with two (2) replications. factor I is the ratio flower banana : wheat flour, that is : J1 = 30%:70%, J2 = 40%:60%, J3 = 50%:50%, dan J4 = 60%:40%. Factor II is  Long Boiling (L) consisting of four levels, that is: L1 = 5 minute, L2 = 10 minute, L3 = 15 minute, dan L4 = 20 minute. The parameters observed: Carbohydrates, protein, fiber, water activity, organoleptic texture, color, and flavor. The statistical analysis was obtained, that ratio flower banana: wheat flour provided highly significant effect (P<0.01) to carbohydrates, protein, fiber, water activity, and organoleptic texture and had no significant effect (P>0.05) on organoleptic color dan flavor. The long boiling provided a highly significant effect (P<0.01) on protein, water activity, organoleptic texture, and color and had no significant effect (P>0.05) on carbohydrates, fiber, and organoleptic flavor. The interaction had no significant effect (P>0.05) on carbohydrates, protein, fiber, water activity, organoleptic texture, color, and flavor.